1976
DOI: 10.1002/pol.1976.170140118
|View full text |Cite
|
Sign up to set email alerts
|

Plasma polymerization of some organic compounds and properties of the polymers

Abstract: Plasma polymerizations (under 13.5‐MHz radiofrequency inductively coupled glow discharge) of some organic compounds are investigated by their properties (elemental analysis, surface energy, and infrared spectra) and their relations to the concentrations of free radicals in the polymers as detected by electron spin resonance (ESR) spectroscopy. Monomers that have been investigated are hexamethyldisiloxane, tetrafluoroethylene, acetylene, acetylene/N2, acetylene/H2O, acetylene/N2/H2O, allene, allene/N2, allene/H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 7 publications
2
48
0
1
Order By: Relevance
“…Yasuda et al, 13 for instance, have shown by using infrared absorption spectroscopy that the hydroxylation of plasma-deposited acetylene films increased continuously for >15 months after deposition. Assuming that such remnant radicals are present also in plasma-treated polymers, exposure of the treated PTFE to air can lead to the incorporation of oxygen, as observed by XPS, via post-plasma reactions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Yasuda et al, 13 for instance, have shown by using infrared absorption spectroscopy that the hydroxylation of plasma-deposited acetylene films increased continuously for >15 months after deposition. Assuming that such remnant radicals are present also in plasma-treated polymers, exposure of the treated PTFE to air can lead to the incorporation of oxygen, as observed by XPS, via post-plasma reactions.…”
Section: Discussionmentioning
confidence: 97%
“…It is worthwhile to comment that free radicals (or dangling bonds) have been observed 10,13 to stay active in plasmadeposited polymeric films for long periods of time. Yasuda et al, 13 for instance, have shown by using infrared absorption spectroscopy that the hydroxylation of plasma-deposited acetylene films increased continuously for >15 months after deposition.…”
Section: Discussionmentioning
confidence: 98%
“…The most widely used spectroscopic tools for analyzing these materials is Fourier transform infrared spectroscopy (FTIR) [1][2][3][4] and electron spectroscopy for chemical analysis (ESCA). 1 -3, 5 Although both techniques are of utility, they have significant limitations.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that ammonia plasmas does not produce primary amine implantation efficiently [26] and accordingly saturated and unsaturated amine-plasmas were suggested to be employed as an alternative [27][28][29][30][31][32][33][34][35]. Successful surface amination of various polymeric substrates were reported, however due to the diversity of plasma reactors, nature of plasma gases and experimental conditions direct comparison of results from these experiments is difficult.…”
Section: Introductionmentioning
confidence: 99%